Are Dentists Hypocrites? Oral Self-care Habits and Self-reported Oral Health Status among Dentists and Non-dentists in Croatia - Marin Vodanović; Antea Barišić; Andrej Šribar; Oliver Šuman (University of Zagreb. School of Dental Medicine, 2024)
Objectives: Dentists provide dental care to their patients and educate them on their oral hygiene and how to maintain oral health. This paper aimed to determine whether dentists are hypocritical when advising their patients on oral hygiene procedures and dental treatments because they do not apply to themselves what they recommend to others. Material and methods: This is a self-reported study conducted through an online survey questionnaire completed by 1001 participants, of whom 551 were non-dentists and 450 dentists. This is the first study on oral hygiene habits and oral status among dentists in Croatia. This research included almost 10% of the total number of working dentists in Croatia. Results: In terms of dental hygiene habits, dentists brushed, flossed and used interdental brushes more frequently, and they also changed toothbrushes more frequently, whereas they attended check-ups less frequently. Dentists also reported a smaller number of teeth with cavities, a greater number of teeth with fillings, a greater number of extracted teeth, and a greater number of dental crowns, but a smaller number of healthy teeth compared to general population. However, dentists had a much higher proportion of participants over 30 years of age, and when subanalysis of participants over 30 years of age was performed, dentists had a greater number of healthy teeth compared to the general population. Conclusions: The results showed that dentists are aware of the importance of their oral health and that they do not pay attention only to their oral hygiene habits, but also apply advice they give their patients. Therefore, they cannot be considered hypocritical.